History of malaria treatment as a predictor of subsequent subclinical parasitaemia: a cross-sectional survey and malaria case records from three villages in Pailin, western Cambodia. - Peto, T; Kloprogge, S; Tripura, R; Nguon, C; Sanann, N; Yok, S; Heng, C; Promnarate, C; Chalk, J; Song, N; Lee, S; Lubell, Y; et al. (BioMed Central, 2016)
Background Treatment of the sub-clinical reservoir of malaria, which may maintain transmission, could be an important component of elimination strategies. The reliable detection of asymptomatic infections with low levels of parasitaemia requires high-volume quantitative polymerase chain reaction (uPCR), which is impractical to conduct on a large scale. It is unknown to what extent sub-clinical parasitaemias originate from recent or older clinical episodes. This study explored the association between clinical history of malaria and subsequent sub-clinical parasitaemia. Methods In June 2013 a cross-sectional survey was conducted in three villages in Pailin, western Cambodia. Demographic and epidemiological data and blood samples were collected. Blood was tested for malaria by high-volume qPCR. Positive samples were analysed by nested PCR to determine the Plasmodium species. To identify previous episodes of malaria, case records were collected from village malaria workers and local health facilities and linked to study participants. Results Among 1343 participants, 40/122 (32.8 %) with a history of clinical malaria were parasitaemic during the cross-sectional survey, compared to 172/1221 (14.1 %) without this history (p < 0.001). Among the 212 parasitaemic participants in the survey, 40 (18.9 %) had a history of clinical malaria, compared to 87 out of 1131 (7.7 %) parasitenegative participants; p < 0.001, adjusted OR 3.3 (95 % CI; 2.1–5.1). A history of Plasmodium vivax was associated with sub-clinical P. vivax parasitaemia in the survey (p < 0.001), but this association was not seen with Plasmodium falciparum (p = 0.253); only three participants had both P. falciparum parasites in the survey and a clinical history of P. falciparum. Conclusions A clinical episode of vivax malaria was associated with subsequent sub-clinical parasitaemia. Treatment of P. vivax with artemisinin-based combination therapy without primaquine often resulted in recurrent episodes. Targeting individuals with a history of clinical malaria will be insufficient to eliminate the sub-clinical reservoir as they constitute a minority of parasitaemias.